Dissociation of anatomical and functional alterations of the default-mode network in first-episode, drug-naive schizophrenia. Issue 12 (December 2015) - Guo, Wenbin; Liu, Feng; Xiao, Changqing; Zhang, Zhikun; Yu, Miaoyu; Liu, Jianrong; Liu, Guiying; Zhao, Jingping
Highlights: A dissociation pattern indicated that brain functional and anatomical abnormalities of the default-mode network (DMN) might be present independently in schizophrenia. The recruitment of first-episode, drug-naive schizophrenia patients offers insight into the pathophysiology of schizophrenia independently of treatment issues. Functional and structural abnormalities highlight the importance of DMN in the pathophysiology of schizophrenia. Abstract: Objective: Anatomical and functional alterations of the default-mode network (DMN) have been implicated in the pathophysiology of schizophrenia. However, no study is engaged to explore whether structural and functional abnormalities of the DMN overlap in schizophrenia. This study was undertaken to examine whether anatomical and functional abnormalities are present in similar or different brain regions of the DMN in first-episode, drug-naive schizophrenia. Methods: Forty-nine first-episode, drug-naive schizophrenia patients and 50 age-, sex-, and education-matched healthy controls underwent structural and resting-state functional magnetic resonance imaging (fMRI) scanning. The voxel-based morphometry (VBM) and fractional amplitude of low-frequency fluctuation (fALFF) methods were used to analyze imaging data. Results: The patients exhibited significantly decreased gray matter volume (GMV) in the left medial prefrontal cortex (orbital part) and increased fALFF in the left posterior cingulate cortex compared with the controls. No overlap of brain regions with anatomical and functional abnormalities was observed in the patient group. There was also no correlation between decreased GMV/increased fALFF and clinical variables in patients. Conclusions: A dissociation pattern of brain regions with anatomical and functional changes within the DMN is revealed in schizophrenia patients. Significance: Our findings suggest that brain functional and anatomical abnormalities within the DMN might contribute independently to the pathophysiology of schizophrenia.